A New Interconnecting Layer of Metal Oxide/Dipole Layer/Metal Oxide for Efficient Tandem Organic Solar Cells. Issue 17 (25th June 2015) - Lu, Shunmian; Guan, Xing; Li, Xinchen; Sha, Wei E. I.; Xie, Fengxian; Liu, Hongchao; Wang, Jiannong; Huang, Fei; Choy, Wallace C. H.
<x xml:space="preserve">Abstract</x> A new metal‐oxide‐based interconnecting layer (ICL) structure of all‐solution processed metal oxide/dipole layer/metal oxide for efficient tandem organic solar cell (OSC) is demonstrated. The dipole layer modifies the work function (WF) of molybdenum oxide (MoOx) to eliminate preexisted counter diode between MoOx and TiO2. Three different amino functionalized water/alcohol soluble conjugated polymers (WSCPs) are studied to show that the WF tuning of MoOx is controllable. Importantly, the results show that S‐shape current density versus voltage (J–V) characteristics form when operation temperature decreases. This implies that thermionic emission within the dipole layer plays critical role for helping recombination of electrons and holes. Meanwhile, the insignificant homotandem open‐circuit voltage (Voc) loss dependence on dipole layer thickness shows that the quantum tunneling effect is weak for efficient electron and hole recombination. Based on this ICL, poly(3‐hexylthiophene) (P3HT)‐based homotandem OSC with 1.20 V Voc and 3.29% power conversion efficiency (PCE) is achieved. Furthermore, high efficiency poly(4, 8‐bis(5‐(2‐ethylhexyl)‐thiophene‐2‐yl)‐benzo[1, 2‐b54, 5‐b9]dithiophene‐alt alkylcarbonylthieno[3, 4‐b]thiophene) (PBDTTT‐C‐T)‐based homotandem OSC with 1.54 V Voc and 8.11% PCE is achieved, with almost 15.53% enhancement compared to its single cell. This metal oxide/dipole layer/metal oxide ICL provides a new strategy to develop other qualified ICL with different hole transporting layer and electron transporting layer in tandem OSCs.